Perception on sight-singing among vocal students at UiTM / Sharifah Amira Syed Mohamad Hafiz - Syed Mohamad Hafiz, Sharifah Amira (2013)
The purpose of this study is to identify the perception of sight-singing among vocal students at UiTM, Shah Alam. This study involved students from Diploma, Degree Education, Degree Performance, and Degree Composition. Objectives of this study were: I) to find out the understanding of sight-singing among vocal students, 2) to investigate the weaknesses of vocal students in sight-singing and 3) To explore ways to improve sight-singing skills among vocal students. The data was collected through questionnaire. As a result, many vocal students at Faculty of Music, Shah Alam did not realize the benefits of sight-singing towards their lessons. The problems of this matter also has been obtained through the questionnaire where they were lack of exercise, did not get formal class for sight-singing, and most of them learnt their new piece by listening to the recordings rather than by sight-singing. There are several ways I suggest to students to improve their sight-singing skill such as starting their vocal class with sight singing. Lecturers can give them simple melodies to help them to get use to sight-singing, involve in ensemble such as choir, they must have sight-singing classes with same importance level such as aural, music theory, and principal class, etc.